Prunetin in a GPR30-dependent manner mitigates renal ischemia/reperfusion injury in rats via interrupting indoxyl sulfate/TLR4/TRIF, RIPK1/RIPK3/MLKL, and RIPK3/PGAM5/DRP-1 crosstalk - Ahmed B. Hamed; Hanan S. El-Abhar; Dalaal M. Abdallah; Kawkab A. Ahmed; Yasmin S. Abulfadl (Elsevier, 2023)
The potential health benefits of phytochemicals in preventing and treating diseases have gained increasing attention. Here, we proved that the methylated isoflavone prunetin possesses a reno-therapeutic effect against renal ischemia/reperfusion (I/R) insult by activating G protein-coupled receptor 30 (GPR30). After choosing the therapeutic dose of prunetin against renal I/R injury in the pilot study, male Sprague Dawley rats were allocated into 5 groups; viz., sham-operated (SO), SO injected with 1 mg/kg prunetin intraperitoneally for three successive days, untreated I/R, I/R treated with prunetin, and I/R treated with G-15, the selective GPR30 blocker, followed by prunetin. Treatment with prunetin reversed the I/R renal injury effect and majorly restored normal renal function and architecture. Mechanistically, prunetin restored the I/R-induced depletion of renal GPR30, an impact that was canceled by the pre-administration of G-15. Additionally, post-administration of prunetin normalized the boosted inflammatory markers indoxyl sulfate, TLR4, and TRIF and abrogated renal cell demise by suppressing necroptotic signaling, verified by the inactivation of p-RIPK1, p-RIPK3, and p-MLKL while normalizing the inhibited caspase-8. Besides, prunetin reversed the I/R-mediated mitochondrial fission by inhibiting the protein expression of PGMA5 and p-DRP-1. All these favorable impacts of prunetin were nullified by G-15. To sum up, prunetin exhibited a significant reno-therapeutic effect evidenced by the enhancement of renal morphology and function, the suppression of the inflammatory cascade indoxyl sulfate/TLR4/TRIF, which turns off the activated/phosphorylated necroptotic trajectory RIPK1/RIPK3/MLKL, while enhancing caspase-8. Additionally, prunetin opposed the mitochondrial fission pathway RIPK3/PGMA5/DRP-1, effects that are mediated via the activation of GPR30.